The Effect of Plasma Treated Water Unit Processes on the Food Quality Characteristics of Fresh-Cut Endive - Schnabel, Uta; Handorf, Oliver; Winter, Hauke; Weihe, Thomas; Weit, Christoph; Schäfer, Jan; Stachowiak, Jörg; Boehm, Daniela; Below, Harald; Bourke, Paula; Ehlbeck, Jörg (Frontiers in Nutrition, 2021)
This study evaluated the impact of a defined plasma treated water (PTW) when applied to various stages within fresh-cut endive processing. The quality characteristic responses were investigated to establish the impact of the PTW unit processes and where PTW may be optimally applied in a model process line to retain or improve produce quality. Different stages of application of PTW within the washing process were investigated and compared to tap water and chlorine dioxide. Fresh-cut endive (Cichorium endivia L.) samples were analyzed for retention of food quality characteristics. Measurements included color, texture and nitrate quantification. Effects on tissue surface and cell organelles were observed through scanning electron and atomic force microscopy. Overall, the endive quality characteristics were retained by incorporating PTW in the washing process. Furthermore, promising results for color and texture characteristics were observed, which were supported by the microscopic assays of the vegetal tissue. While ion chromatography detected high concentrations of nitrite and nitrate in PTW, these did not affect the nitrate concentration of the lettuce tissue post-processing and were below the concentrations within EU regulations. These results provide a pathway to scale up the industrial application of PTW to improve and retain quality characteristic retention of fresh leafy products, whilst also harnessing the plasma functionalized water as a process intervention for reducing microbial load at multiple points, whether on the food surface, within the process water or on food-processing surfaces.